Criteria for the introduction into practice of technologies for motivating students as socially active individuals (Texas Journal of Engineering and Technology, 2022)
This article outlines the basics of introducing pedagogical technologies into the educational process of forming students as socially active individuals. Education is aimed at the realization of the tasks set and the scientific hypotheses put forward in the concept, system, program, object, subject, etc.